Ascorbic acid sensor based on ZnO/B(PM-PA) nanocomposite - lakshmi, P. Pon Maha; Rajakani, P.; C.Vedhi, C.Vedhi (Journal of Neonatal Surgery, 2025)
Recent years have seen a rise in interest in polymer nanocomposites based on electroactive conducting polymers with nanoparticle fillers because of their highly desirable multifunctional characteristics. A precise and considerate evaluation of AA is essential in the diagnosis of several mental disorders. Determining its presence in biological samples is still challenging since it coexists with other high-concentration biomolecules. We introduce a facile, eco-friendly Sensor B(PM-PA) Polymer blend (PB) and ZnO/B(PM-PA) nanocomposite (NCP). Analytical methods, including FT-IR, XRD analysis, and UV-Vis, were employed to explain these nanocomposites. A novel B(PM-PA)/ ZnO electrochemical biosensor was introduced for the in vivo detection of ascorbic acid. In addition, the electrocatalytic reduction of AA on PB&NCP was briefly investigated and achieved good analytical performance with an excellent linear range (0.03-0.1 µM), and a low detection limit (1.14mM&0.44µM). Therefore, the finding of PB&NCP nanocomposite can be regarded as an effective catalyst to enhance the AA detection